2000
DOI: 10.1029/1999jc900295
|View full text |Cite
|
Sign up to set email alerts
|

Blending HF radar and model velocities in Monterey Bay through normal mode analysis

Abstract: Although model simulations that assimilated the radar observations produced currents that were in general agreement with the pattern seen in the radar data, Lewis et al. [1998] expressed concern that errors in the radar data could cause problems in the simulations. Horizontal divergences calculated from the radar data showed unrealistically large magnitudes, changes in sign from time step to time step, and little coherence between adjacent grid cells. These horizontal divergence patterns, when assimilated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 13 publications
2
73
0
Order By: Relevance
“…To overcome these data gaps, various interpolation techniques have been applied to HF radar total vector fields. These algorithms that include 2DVAR (Yaremchuk and Sentchev 2009), normal modes (Lipphardt et al 2000), open modal analysis (Kaplan and Lekien 2007), and statistical mapping (Barrick et al 2012;O'Donnell et al 2005) have largely been applied to the UWLS surface current maps after the UWLS combination. Recently, Kim et al (2007) introduced a method that interpolates data as part of the combination step from radial component vectors to total vector maps.…”
Section: Hf Radar Processingmentioning
confidence: 99%
“…To overcome these data gaps, various interpolation techniques have been applied to HF radar total vector fields. These algorithms that include 2DVAR (Yaremchuk and Sentchev 2009), normal modes (Lipphardt et al 2000), open modal analysis (Kaplan and Lekien 2007), and statistical mapping (Barrick et al 2012;O'Donnell et al 2005) have largely been applied to the UWLS surface current maps after the UWLS combination. Recently, Kim et al (2007) introduced a method that interpolates data as part of the combination step from radial component vectors to total vector maps.…”
Section: Hf Radar Processingmentioning
confidence: 99%
“…Our study uses the MZD to construct appropriate EOFs for the analysis of the spatio-temporal structure of the model attractor at 50 m depth. Other oceanographic applications of MZD can be found in Eremeev et al (1992), Lipphardt et al (2000) and Chu et al (2003a, b) selected as examples.…”
Section: Toroidal and Poloidal Eof Decompositionmentioning
confidence: 99%
“…This influx is due to numerous methods of data collection which are being implemented: HF or high frequency radar, Lagrangian drifters, synthetic aperture radar, new generation passive remote-sensing platforms and towed arrays which can collect information on current velocity fields of a ship's wake . 1 This gives scientists a significantly improved picture of current flow throughout many coastal regions.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In the paper by Eremeev, the data was received from autonomous drifting buoys (ADB) in the Black Sea was used to extrapolate velocity fields for this closed body of water using what was later termed by Lipphardt as normal mode analysis (NMA). 4,5 Eremeev and his collaborators found that this process allowed him to model the large scale currents measured by the ADB's with a relatively small number of modes. One set of data required only 76 modes and yet still accounted for 70% of the kinetic energy associated with the observed field.…”
Section: Introductionmentioning
confidence: 99%